2025年2月4日 星期二

多項式,已知餘數,求商

 GPT Icon

We are given the function:

f(x)=(4x22x+1)(mx+n)+4x9f(x) = (4x^2 - 2x + 1)(mx + n) + 4x - 9

with the conditions:

f(12)=5,f(1)=8.f\left(-\frac{1}{2}\right) = -5, \quad f(1) = -8.

We need to determine mm and nn, and then compute f(2)f(2).


Step 1: Compute f(12)f(-\frac{1}{2})

Substituting x=12x = -\frac{1}{2}:

4(12)22(12)+1=4(14)+1+1=1+1+1=3.4\left(-\frac{1}{2}\right)^2 - 2\left(-\frac{1}{2}\right) + 1 = 4\left(\frac{1}{4}\right) + 1 + 1 = 1 + 1 + 1 = 3.
f(12)=(3)(m(12)+n)+4(12)9f\left(-\frac{1}{2}\right) = (3)(m(-\frac{1}{2}) + n) + 4(-\frac{1}{2}) - 9
=3(m2+n)29= 3\left(-\frac{m}{2} + n\right) - 2 - 9
=3n3m211= 3n - \frac{3m}{2} - 11

Setting this equal to 5-5:

3n3m211=53n - \frac{3m}{2} - 11 = -5
3n3m2=63n - \frac{3m}{2} = 6
3n=3m2+63n = \frac{3m}{2} + 6
n=m2+2n = \frac{m}{2} + 2

Step 2: Compute f(1)f(1)

Substituting x=1x = 1:

4(1)22(1)+1=42+1=3.4(1)^2 - 2(1) + 1 = 4 - 2 + 1 = 3.
f(1)=3(m(1)+n)+4(1)9f(1) = 3(m(1) + n) + 4(1) - 9
=3(m+n)+49= 3(m + n) + 4 - 9
=3m+3n5= 3m + 3n - 5

Setting this equal to 8-8:

3m+3n5=83m + 3n - 5 = -8
3m+3n=33m + 3n = -3
m+n=1m + n = -1

Step 3: Solve for mm and nn

We have the system:

  1. n=m2+2n = \frac{m}{2} + 2
  2. m+n=1m + n = -1

Substituting equation (1) into equation (2):

m+(m2+2)=1m + \left(\frac{m}{2} + 2\right) = -1
m+m2+2=1m + \frac{m}{2} + 2 = -1

Multiply everything by 2 to clear the fraction:

2m+m+4=22m + m + 4 = -2
3m=63m = -6
m=2m = -2

Substituting m=2m = -2 into n=m2+2:

n=22+2=1+2=1n = \frac{-2}{2} + 2 = -1 + 2 = 1

Thus, we have:

m=2,n=1.m = -2, \quad n = 1.

Step 4: Compute f(2)f(2)

Substituting x=2x = 2:

4(2)22(2)+1=164+1=13.4(2)^2 - 2(2) + 1 = 16 - 4 + 1 = 13.
f(2)=(13)(m(2)+n)+4(2)9f(2) = (13)(m(2) + n) + 4(2) - 9
=13(2(2)+1)+89= 13(-2(2) + 1) + 8 - 9
=13(4+1)+89= 13(-4 + 1) + 8 - 9
=13(3)+89= 13(-3) + 8 - 9
=39+89= -39 + 8 - 9
=40= -40

Final Answer

40

沒有留言:

張貼留言